Breaking barriers: gender diversity and environmental identity in Pakistan's ranger workforce - Aisha, Hamera; Aziz, Rizwana; Sharif, Faiza; Thielen, Britt; Singh, Rohit; Anbarin, Haseena; Naseem, Fareeha; Tahir, Rabia (Frontiers in Sociology, 2025)
Gender diversity enhances conservation outcomes by fostering inclusive decision-making and more effective policies. This study presents Pakistan's first national, gender-disaggregated analysis of its biodiversity conservation ranger workforce, examining women's perceptions, diversity barriers, and how ranger roles shape environmental identity and place attachment,. Using a mixed-method approach, we engaged 49 female and 191 male rangers, employers, and officials from wildlife, forest, and fisheries departments across all provinces and territories. Findings reveal a stark gender imbalance, with women constituting 2.6 percent of the workforce. Female rangers reported stronger biodiversity protection motivation and environmental identity, yet perceived far less acceptance in their departments. Key barriers included the male-dominated image of the profession, non-inclusive policies, recruitment biases, social and family restrictions, absence of female role models, and safety concerns. Despite their strong commitment, women disproportionately face inadequate resources, ill-fitting equipment, safety risks, and work-life balance challenges. Addressing these systemic barriers requires embedding gender equity in recruitment, promotion, and training. Workplace policies must ensure proper equipment, safety, and accommodations, while fostering an enabling environment that recognizes and supports women's contributions. Embedding gender diversity in conservation is essential for building a resilient and sustainable ranger workforce capable of delivering biodiversity and climate goals.